How Do Trade and Communication Costs Shape the Spatial Organization of Firms? - Toshitaka Gokan; Sergey Kichko; Jacques-Francois Thisse (Center for Economic Studies and ifo Institute (CESifo), 2019)
We consider an economic geography setting in which firms are free to choose one of the following organizational types: (i) integrated firms, which perform all their activities at the same location, (ii) horizontal firms, which operate several plants producing the same good at different locations, and (iii) vertical firms, which perform distinct activities at separated locations. We show that there exists a unique organizational equilibrium, which typically involves the coexistence of various organizational forms. We also give necessary and sufficient conditions for the three types of firms to coexist within the same region and show that transportation and communication costs have opposite effects on firms' organizational choices. This suggests that, depending on its nature, the supply of a new transportation infrastructure may lead to contrasted locational patterns.
Keywords: F12; F21; R12; 330; region; transportation costs; communication costs; horizontal firm; vertical firm